(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
With the recognition of content discoverability and information analytics in the scientific publishing industry, more and more effort is dedicated to digitization and automated analysis of scholarly publications. As part of this effort, the authors research data journal for the humanities and social sciences 9 (2024) 1–21 designed a pipeline to extract structured information from bibliography and index lists of existing scholarly publications, as well as to disambiguate and export it as linked data. In this article, the authors present the Brill Knowledge Graph (kg), obtained by applying this pipeline to a corpus of books in the Arts, Humanities and Social Sciences (ahss) provided by the publisher Brill.